Multi-omics insights into potential mechanism of SGLT2 inhibitors cardiovascular benefit in diabetic cardiomyopathy - Xi, Yangbo; Chen, Dongping; Dong, Zhihui; Zhang, Jinhua; Lam, Hingcheung; He, Jiading; Du, Keyi; Chen, Can; Guo, Jun; Xiao, Jianmin (Frontiers in Cardiovascular Medicine, 2022)
Background Metabolic and energy disorders are thought to be central to the etiology of diabetic cardiomyopathy (DCM). Sodium glucose cotransporter 2 inhibitors (SGLT2i) can effectively reduce the risk of cardiovascular death and heart failure in DCM patients, but the underlying mechanism has not been elucidated. Methods We established a DCM rat model followed by treatment with empagliflozin (EMPA) for 12 weeks. Echocardiography, blood tests, histopathology and transmission electron microscopy were used to evaluated the phenotypic characteristics of the rats. The proteomics and metabolomics of the myocardium in the rat model was performed to identify the potential targets and signaling pathways associated with the cardiovascular benefit of SGLT2i. Results The diabetic rat showed pronounced DCM characterized by mitochondrial pleomorphic, impaired lipid metabolism, myocardial fibrosis and associated diastolic and systolic functional impairments in the heart. To some extent, these changes were ameliorated after treatment with EMPA. A total of 43 proteins and 34 metabolites were identified as targets in the myocardium of diabetic rats treated with EMPA. The KEGG analysis showed that arachidonic acid is associated with the maximum number of related pathways and may be a potential target of EMPA treatment. Fatty acid metabolism enhanced in diabetic heart, and the perturbation of biosynthesis of unsaturated fatty acids and arachidonic acid metabolism was a potential enabler for the cardiovascular benefit of EMPA. Conclusion SGLT2i ameliorated lipid accumulation and mitochondrial damage in the myocardium of diabetic rats. The metabolomic and proteomic data revealed the potential targets and signaling pathways associated with the cardiovascular benefit of SGLT2i, which provides a valuable resource for the mechanism of SGLT2i.